1961
DOI: 10.1111/j.1478-4408.1961.tb02398.x
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption of Non‐ionic Dyes by Cellulose

Abstract: Linear isotherms have been obtained on viscose rayon, in the range 20-90"C, with benzidine, 0-and o-Tolidine has much higher affinity for cellulose than Non-m-tolidine, and derivatives of arninoazobenzene. the non-coplanar m-tolidine. ionic dyes do not appear t o forni aygregat,rs in aqueous solution.Heats of dyeing were found to be comtant, between 40 and 80°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 4 publications
4
24
0
Order By: Relevance
“…From the perspective of the disperse dye/PET fibre system, in 1954, Schuler and Remington 18 observed that rectilinear, Nernst (aka partition) adsorption isotherms were obtained for the aqueous CI Disperse Red 15/PET fibre system which took the generic form of line I in Figure 1. These findings were subsequently confirmed by other workers for the disperse dye/PET fibre system 19,[22][23][24] as well as for the adsorption of disperse dyes on other types of fibre (e.g., PA, 22,25,26 PP, 27 CA 8,19,[28][29][30] PAN, 31,32 CV, 33 CTA 30 and wool 34 ; see Burkinshaw 5 for a summary).…”
Section: Thermodynamic Analysis Of the Aqueous Disperse Dye Adsorptio...supporting
confidence: 71%
See 1 more Smart Citation
“…From the perspective of the disperse dye/PET fibre system, in 1954, Schuler and Remington 18 observed that rectilinear, Nernst (aka partition) adsorption isotherms were obtained for the aqueous CI Disperse Red 15/PET fibre system which took the generic form of line I in Figure 1. These findings were subsequently confirmed by other workers for the disperse dye/PET fibre system 19,[22][23][24] as well as for the adsorption of disperse dyes on other types of fibre (e.g., PA, 22,25,26 PP, 27 CA 8,19,[28][29][30] PAN, 31,32 CV, 33 CTA 30 and wool 34 ; see Burkinshaw 5 for a summary).…”
Section: Thermodynamic Analysis Of the Aqueous Disperse Dye Adsorptio...supporting
confidence: 71%
“…Firstly, linear adsorption isotherms of the type represented by line I in Figure 1 have been secured for the equilibrium uptake of disperse dyes on a wide range of different types of textile fibre (e.g., PET, cotton, wool, PAN, CV, etc. ), 15,18,27,[31][32][33][34] which of course contain a broad assortment of potential adsorption sites (e.g., -OH, -NH 2 , -COOH, -SO 3 H, -OCOCH 3 , etc.) with which sorbed dye molecules can interact and eventually become adsorbed onto.…”
Section: Dye Saturation In the Fibre Phase S Fmentioning
confidence: 99%
“…Despite the many differences between cotton, PA 66 and PET fibres, it is widely assumed that the mechanism of disperse dye adsorption described earlier in the case of PET fibres 2 applies to each of these three types of textile fibre (eg, [4][5][6][7][8] ). This all-encompassing mechanistic assumption therefore tacitly presupposes that the manner by which disperse dyes interact with PET, cotton and PA 66 substrates is identical, which implies that the particular physico-chemical characteristics responsible for disperse dye-fibre substantivity and the forces of interaction that govern both the diffusivity of the dyes and their adsorption within the different types of fibre, are also identical.…”
Section: Introductionmentioning
confidence: 99%
“…It can provide high durability to fabrics, because nanoparticles have a large surface areato-volume ratio and high surface energy, thus presenting better affinity for fabrics and leading to an increase in durability of the function [7].…”
Section: Introductionmentioning
confidence: 99%